Weight and height influence on first permanent molar’s eruption age - Arasai Almaguer Berberena; Georgina Jiménez Estrada; Adys Castro Barberena; Idalgis Sánchez Reyes; Laura Naranjo Hernández; Liliana Paz Milián (Medisur)
Foundation: dental eruption is a biological process of a dental organ migration from the period of tooth formation until it reaches the occlusion plane. Objective: determine the relationship between weight, height and the first permanent molar eruption as events of somatic growth in six-years-old children. Methods: descriptive cross-sectional observational study carried out at the Antonio Maceo Grajales school in the Cienfuegos municipality, from September 2020 to June 2021, which included 62 schoolchildren. The data were obtained through anthropometric sheets. Variables such as age, sex, skin color, weight, height and time of first molar eruption were analyzed. The collected data were located in statistical charts designed for this purpose with Excel XP and Microsoft Word 2010 was used as a text editor. Results: when relating percentiles of weight to height, eruption of molar number six and sex, it was observed that 21 females with normal weight had erupted the first molar (33.3% of the total number of children) and 13 normal weight males, out of a total of 25 , did not present signs of molar number six in the mouth (20.6% of the total). Height behaved within normal percentiles. Conclusions: the children in the sample studied have a delay in the first permanent molar eruption, without this being related to weight and height. The delay was more observed in men.